2020
DOI: 10.1016/j.lungcan.2020.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and lung cancer: A greater fatality rate?

Abstract: Background: Currently there are no reported series determining the Covid-19 infected lung cancer patient´s characteristics and outcome that allow us to clarify strategies to protect our patients. In our study we determine whether exists differences in cumulative incidence and severity of Covid-19 infection between lung cancer patients visiting our Medical Oncology department and the reference population of our center (320,000 people), in the current epicenter of the pandemic in Europe (Madrid, Spain). We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
108
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 9 publications
(16 reference statements)
8
108
0
6
Order By: Relevance
“…Additionally, there are a number of patients at higher risk for COVID-19 infection, including patients with cancer, transplants, or other conditions [ 3 ]. In this case, people with a lung cancer and smoking/vaping history may be remain an important vulnerable population [ 4 , 5 ]. Lung cancer patients are very susceptible for getting respiratory infections and most of them are detected with chronic obstructive pulmonary disease (COPD) as well as metastatic disease, so it is expected to observe greater mortality or at least greater severity of the infectious symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are a number of patients at higher risk for COVID-19 infection, including patients with cancer, transplants, or other conditions [ 3 ]. In this case, people with a lung cancer and smoking/vaping history may be remain an important vulnerable population [ 4 , 5 ]. Lung cancer patients are very susceptible for getting respiratory infections and most of them are detected with chronic obstructive pulmonary disease (COPD) as well as metastatic disease, so it is expected to observe greater mortality or at least greater severity of the infectious symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with lung cancer, a rapid progression of COVID-19, as well as the development of serious anoxia, is often observed [ 5 ]. A plethora of studies have espoused the notion that a significant mortality rate is observed in individuals with lung cancer with COVID-19 compared to all COVID-19 patients, with a 52.3% mortality rate in the analyzed subgroup of cancer patients [ 6 ]. In addition to suboptimal pulmonary functions, most lung cancer patients are also on chemotherapy, which further enervates their immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Rogado J et al [7] reported a signi cant increase in the mortality rate in lung cancer patients with Covid-19 compared to all Covid-19 patients, which may be due to a greater predisposition to respiratory infections and a previous diagnosis of COPD and metastatic disease in lung cancer patients. Therefore, providing care to patients with lung cancer has been challenging [8] .…”
Section: Introductionmentioning
confidence: 99%